Voda v prsti in ugotavljanje njenega razporejanja v odvisnosti od reliefa - Repe, Blaž (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
There is very little soil water data in Slovenia. Most of them point oriented and is therefore very difficult to generalize on larger areas. The distribution of soil water was estimated using relief data. For quantitative measure of soil water topographical wetness index (TWI) had been used. Topographical wetness index shows water accumulation in a given location and is a function of slope and upslope specific catchment area.
Keywords: geomorfologija; geomorphology; pedogeografija; relief; topography; prst (pedologija); tla; voda; vlaga; razporeditev; vlažnost tal; Slovenia; Slovenija